1987
DOI: 10.3406/paleo.1987.4416
|View full text |Cite
|
Sign up to set email alerts
|

The Desert "Kites" of the Badiyat Esh-Sham and North Arabia

Abstract: Archaeological investigations into the steppic regions of the Near East have only recently been systematized in controlled surveys and excavations. Prior to this information regarding pastoral nomads and 'archaeological' remains came from travellers' accounts. One corpus of such data concerned extensive stone structures in the basaltic sub-region of the Badiyat esh-Sham, 'desert kites', which have received much speculative attention. Their function and date were not established in any empirical way until very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 3 publications
2
100
0
2
Order By: Relevance
“…It has been argued that the construction and use of these kites dates as far back as 8000-9000 y ago during the Pre-Pottery Neolithic B, when hunted gazelle were still the primary source of protein for steppic peoples (13). Gazelle remains from the site of Abu Hureyra in the middle Euphrates Valley (14,15) have yielded demographic data interpreted as evidence for early mass kills using kites or other communal hunting techniques (see also ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that the construction and use of these kites dates as far back as 8000-9000 y ago during the Pre-Pottery Neolithic B, when hunted gazelle were still the primary source of protein for steppic peoples (13). Gazelle remains from the site of Abu Hureyra in the middle Euphrates Valley (14,15) have yielded demographic data interpreted as evidence for early mass kills using kites or other communal hunting techniques (see also ref.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that the mass harvesting of Persian gazelle using "desert kites" might have played a role in their extirpation (13)(14)(15). These enigmatic stone structures can be found in large numbers from Arabia to southeastern Turkey along a proposed former migratory route for this species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the southern Levant, drive and surround hunting could have been accomplished by taking advantage of the natural topography, as well as cultural features described as desert 'kites' that served as enclosures during game drives [47].…”
Section: Implications and Importancementioning
confidence: 99%
“…Kites have been discovered in the Middle East since the 1920s. Despite several studies, the issues related to their age and function remain without satisfactory answers [4,8]. The kites are thus an underestimated phenomenon.…”
Section: Background An Motivationmentioning
confidence: 99%